Asuhan Keperawatan Pada Pasien Post Operasi Open Reduction And Internal Fixation (ORIF): Fraktur Supracondylar Femur Dextra Dengan Gangguan Mobilitas Fisik Dan Gangguan Integritas Kulit - Dea Agustina Zalianty; Tati Karyawati (STIKES Columbia Asia Medan, 2026)
Fractures are one of the most common musculoskeletal disorders caused by trauma, repetitive stress, or pathological factors. Supracondylar femur fracture is a type of femur fracture occurring at the distal 12 cm of the femur, and Open Reduction and Internal Fixation (ORIF) is the primary surgical intervention. Post-operative ORIF patients commonly experience impaired physical mobility and impaired skin integrity. This study aimed to provide comprehensive nursing care to a patient post-ORIF for right supracondylar femur fracture in the Mawar 2 Ward of RSUD dr. Soeselo, Tegal Regency. A descriptive method with a nursing process approach was used, employing interview, observation, documentation study, and literature study. Nursing assessments conducted on February 8, 2026 revealed that the patient (Ny. S, female, 68 years) experienced pain at the surgical site with a scale of 7, inability to move both lower extremities (muscle strength score 2), and a post-operative wound approximately 10 cm in length with redness and edema. Two nursing diagnoses were established: impaired physical mobility related to neuromuscular disorders and impaired structural bone integrity, and impaired skin/tissue integrity related to invasive procedure effects. Nursing interventions included mobilization support, pain management, wound care, and collaborative administration of medical therapy. After two days of nursing implementation, both diagnoses were partially resolved. Discharge planning focused on gradual mobilization, independent wound care, and high-protein and high-calorie diet to accelerate recovery.